Building a Multi-layered Support System for Students in Psychological Distress: Insights from Indonesian Faculty Members - Putri, Adelia Khrisna; Saputra, Axel Rizqy; Yahya, Anna Nadia Febrina (Jurnal Psikologi, 2023)
Recent studies have noted a rising prevalence of common mental health issues, including suicidal ideation and self-harming behaviors, among college students globally. However, limited attention has been given to the preparedness of educational institutions in addressing these concerns. This study aims to comprehensively assess the landscape of mental health support within Indonesian universities, with a particular focus on uncovering the availability of policies and training as well as faculty members’ perceptions of students’ mental health challenges, the identification of responsible parties for providing assistance, and the specific support needs of faculty members prior to the pandemic. Employing a mixed exploratory method, the research engaged 172 faculty members from 72 universities in Indonesia who completed an online survey. The quantitative data underwent descriptive analysis, while the free-text responses were thematically categorized. The findings revealed that (1) most universities still lack formal policies on dealing with students in psychological distress; (2) there is a gap between faculty members’ willingness to discuss students’ mental health and their decision to refer students to mental health services; and (3) there is a necessity for building a multi-layered support system for this issue. Hence, universities are advised to proactively institute formal policies to address students in psychological distress, implement comprehensive mental health training for both students and faculty, and enhance the accessibility of professional psychological support services, thereby creating a robust framework for promoting and safeguarding the mental well-being of students.